CD123-directed allogeneic chimeric-antigen receptor T-cell therapy (CAR-T) in blastic plasmacytoid dendritic cell neoplasm (BPDCN): Clinicopathological insights. (October 2022) - Pemmaraju, Naveen; Wilson, Nathaniel R.; Senapati, Jayastu; Economides, Minas P.; Guzman, Monica L.; Neelapu, Sattva S.; Kazemimood, Rossana; Davis, Richard Eric; Jain, Nitin; Khoury, Joseph D.; Sugita, Mayumi; Cai, Tianyu; et al.
Abstract: Purpose: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a hematologic malignancy associated with overexpression of CD123. Allogeneic chimeric antigen receptor T cells (CAR-T) directed against CD123 in BPDCN have been studied in clinical trials. We performed post-mortem analysis of a patient treated with anti-CD123 CAR-T to elucidate cause of death, development of cytokine release syndrome (CRS), and tissue distribution of UCART123 cells. Methods: A post-mortem multidisciplinary clinicopathologic analysis was performed with digital droplet polymerase chain reaction of isolated blood and tissue ribonucleic acid (RNA) to evaluate tissue distribution of infused CAR-T. Multiparameter flow cytometry for detection of CAR-T was used for whole blood samples. Cytokine levels in plasma were measured using multiplex bead assay. Gene expression profiling on isolated RNA was performed using semi-custom Nanostring immune gene panel and RNA-sequence method. RNA in situ hybridization was performed using CAR-specific probe. Results: The patient developed severe clinical CRS refractory to corticosteroids, tocilizumab, and lymphodepletion. Despite significant reduction in BPDCN lesions, the patient passed away on day 9 of CAR-T. Autopsy results show that following lymphodepletion and UCART123 administration, the patient remained severely lymphopenic with few UCART123 cells detected, predominantly localized to spleen. Conclusions: No definitive cause of death was determined, but we hypothesized that the patient may have succumbed to CAR-T-mediated cardiopulmonary toxicity. UCART123 cells displayed low overall distribution, with predominance in immune organs and tissues. Mechanism of CRS development is still poorly understood in patients receiving CAR-T therapy. Future directions in the field developing CD123-targeted agents in BPDCN are discussed. Highlights: First report of clinicopathologic insights from autopsy after UCART123 in BPDCN. Comprehensive multi-disciplinary analysis, including cytokine and molecular profiling. Patient died due to CRS which was refractory to corticosteroid and anti-IL-6 therapy. Few UCART123 cells were found on autopsy tissues, predominantly localized in spleen.